Finding safe dose-volume constraints for re-irradiation with SBRT of patients with prostate cancer relapse: The IEO experience. (December 2021) - Augugliaro, Matteo; Marvaso, Giulia; Cambria, Raffaella; Pepa, Matteo; Bagnardi, Vincenzo; Frassoni, Samuele; Pansini, Floriana; Patricia Rojas, Damaris; Colombo, Francesca; Iuliana Fodor, Cristiana; Musi, Gennaro; Petralia, Giuseppe; et al.
Highlights: Consensus for the management of PCa recurrence following EBRT is lacking. Salvage SBRT represents an effective and safe treatment option. Literature on dosimetric constraints for safe and effective re-irradiation is scarce. The study provides a useful benchmark for re-irradiation planning. Abstract: Aim: The primary aim of this study is to provide preliminary indications for safe constraints of rectum and bladder in patients re-irradiated with stereotactic body RT (SBRT). Methods: Data from patients treated for prostate cancer (PCa) and intraprostatic relapse, from 1998 to 2016, were retrospectively collected. First RT course was delivered with 3D conformal RT techniques, SBRT or volumetric modulated arc therapy (VMAT). All patients underwent re-irradiation with SBRT with heavy hypofractionated schedules. Cumulative dose-volume values to organs at risk (OARs) were computed and possible correlation with developed toxicities was investigated. Results: Twenty-six patients were included. Median age at re-irradiation was 75 years, mean interval between the two RT courses was 5.6 years and the median follow-up was 47.7 months (13.4–114.3 months). After re-irradiation, acute and late G ≥ 2 GU toxicity events were reported in 3 (12%) and 10 (38%) patients, respectively, while late G ≥ 2 GI events were reported in 4 (15%) patients. No acute G ≥ 2 GI side effects were registered. Patients receiving an equivalent uniform dose of the two RT treatments < 131 Gy appeared to be at higher risk of progression (4-yr b-PFS: 19% vs 33%, p = 0.145). Cumulative re-irradiation constraints that appear to be safe are D30% < 57.9 Gy for bladder and D30% < 66.0 Gy, D60 % < 38.0 Gy and V122.1 Gy  < 5% for rectum. Conclusion: Preliminary re-irradiation constraints for bladder and rectum have been reported. Our preliminary investigation may serve to clear some grey areas of PCa re-irradiation.